Egypt’s Red Sea Coast: Phylogenetic analysis of cultured microbial consortia in industrialized sites - Mustafa, Ghada A.; Abd-Elgawad, Amr; Abdel Haleem, Alyaa M.; Siam, Rania (Frontiers in Microbiology, 2014)
The Red Sea has a unique geography and ecosystem and its shores are very rich in mangrove, macro-algae and coral reefs. Different sources of pollution are affecting the Red Sea shores and waters which impacts biological life including microbial life. We assessed the effects of industrialization, along the Egyptian Red Sea coast in eight coastal sites and two lakes, on microbial life. The bacterial community in sediment samples was analyzed using bacterial 16S rDNApyrosequencing of V6-V4 hypervariable regions. Taxonomical assignment of 131,402 significant reads to major bacterial taxa revealed five main bacterial phyla dominating the sampled Red Sea sites. This includes Proteobacteria (68%), Firmicutes (13%), Fusobacteria (12%), Bacteriodetes (6%) and Spirochetes (0.03%). Further analysis revealed distinct bacterial consortium formed mainly of: 1) marine Vibrio’s- suggesting a “Marine Vibrio phenomenon” 2) potential human pathogens and 3) oil-degrading bacteria. We discuss a distinct microbial consortium in Solar Lake West near Taba/Eilat and Saline Lake in Ras Muhammad; revealing the highest abundance of human pathogens versus no pathogens, respectively. Our results draw attention to the affects of industrialization on the Red Sea, and suggest further analysis to overcome hazardous affects on the impacted sites.